High bone turnover status as a risk factor in symptomatic hypocalcemia following denosumab treatment in a male patient with osteoporosis - Ishikawa K (Dove Medical Press, 2018)
Koji Ishikawa,1–3 Takashi Nagai,1 Koki Tsuchiya,1 Yusuke Oshita,3 Takuma Kuroda,1 Hiroshi Ito,1 Soji Tani,1 Yusuke Dodo,1 Tomoaki Toyone,1 Katsunori Inagaki1 1Department of Orthopaedic Surgery, Showa University School of Medicine, Tokyo, Japan; 2Department of Orthopaedic and Spine Surgery, Sanraku Hospital, Tokyo, Japan; 3Department of Orthopaedic Surgery, Yamanashi Red Cross Hospital, Yamanashi, Japan Abstract: Denosumab is a fully human monoclonal antibody against the receptor activator of nuclear factor-κB ligand (RANKL) that is used for the treatment of osteoporosis. Denosumab-induced hypocalcemia is a rare but important adverse event, which is usually asymptomatic in patients with osteoporosis. It is also known that hypocalcemia is common in patients with bone metastases and severe renal impairment. Here we report a case of symptomatic hypocalcemia following administration of 60 mg of denosumab in a patient with high bone turnover and no renal impairment (estimated glomerular filtration rate [eGFR], 71 mL/min), despite prophylactic oral vitamin D administration. This report supports our observation that there is a risk of protracted and marked denosumab-induced hypocalcemia in patients with high bone turnover, irrespective of their degree of renal impairment. Keywords: denosumab, symptomatic hypocalcemia, high bone turnover, no renal impairment